I am not going to get up today! - Seuss, Dr.; Stevenson, James, 1929-2017 (New York : Beginner Books, 1987)
A boy is so sleepy that he vows nothing will get him out of his morning bed, neither peas and beans nor the United States Marines.
Previously published without accompanying cassette.
One side of cassette for reading along, other side for listening only.
Keywords: Sleep -- Fiction; Beds -- Fiction; Stories in rhyme; Humorous stories